Energy Security in Malaysia: a Quantitative Analysis - Sahid, Endang Jati Mat (International Journal of Engineering and Technology, 2018)
This paper examines the security of energy supply in Malaysia.  Analytical framework was used to quantify and assess the progress of energy security of Malaysia in four different categories namely Availability, Applicability, Affordability and Acceptability of energy resources.  Key metrics include the documentation of energy reserves, energy access, and CO2 emissions from year 2005 to 2015.  Relevant energy security indicators for Malaysia were identified using high quality historical data from World Bank and Energy Commission.The evaluation findings show that Malaysia has experienced a significant improvement in Applicability dimension, while Availability and Acceptability aspects of energy security only registered slight improvements.  On the other hand, Affordability dimension has suffered a slight decline.  This study suggests that diversifying energy sources, efficient utilization of energy and reducing carbon content of energy could be enhanced to improve energy security level in Malaysia.Energy security indicator; Energy policy; Malaysia, Security of supply